Menerapkan Dan Meningkatkan Mutu Belajar Baca Pada Anak Di Panti Asuhan - Najmi Laili Hasibuan; Malida Putri (Yayasan Literasi Sains Indonesia, 2022)
lmplementing the quality of learning to read in children is very impotant because the ability to read is something that is vital in an educated society. Howover, children who do not understand the importanceof learning to read will not be a motivated to learn. Thus the importance of learning to read for yourself will be a source of information or opportunities for the future. This is found in children at the Stergein Haga Indonesia Orphanage who need help to increase interest in learning to read. In the process of assistance provided, it was carried out in PKL I mini project activies, using the Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation, and Termination. The process of solving client problems is to apply the quality of learning to read in children which is one strategy to increase children's interest in learning to read.